Rhythm & revolt tales of the Antilles - Breton, Marcela (New York, New York Penguin Group, 1995)
Tales by Caribbean writers. They range from Cloud Cover Caribbean by Ana Lydia Vega, on national rivalry, to The Cow on the Rooftop by Lino Novas Calvo, in which a mother kills a son over food.
Cloud cover Caribbean / Ana Lydia Vega (Puerto Rico) -- The singing turtle / Philippe Thoby-Marcelin and Pierre Marcelin (Haiti) -- The hill of Mambiala / Lydia Cabrera (Cuba) -- Pioneers, oh pioneers / Jean Rhys (Dominica) -- The strange burial of Sue / Claude McKay (Jamaica) -- The gratuity / Seepersad Naipaul (Trinidad) -- Calypsonian / Samuel Selvon (Trinidad) -- Enchanted alley / Michael Anthony (Trinidad) -- Black sun / Emilio Díaz Valcárcel (Puerto Rico) -- At the great ecbo / Guillermo Cabrera Infante (Cuba) -- My aunt Gold Teeth / V.S. Naipaul (Trinidad) -- The wharf rats / Eric Walrond (Guyana) -- The cow on the rooftop / Lino Novás Calvo (Cuba) -- Caribbean Siren / Fanny Buitrago (Colombia) -- Red hot peppers / Patrick Chamoiseau (Martinique) -- Etc. / Luis Rafael Sánchez (Puerto Rico) -- A walk to the jetty / Jamaica Kincaid (Antigua) -- From the ocean floor / Edwidge Danticat (Haiti) -- Hallelujah for a woman-garden / René Depestre -- The beautiful soul of Don Damián / Juan Bosch (Dominican Republic) -- The sign of winter / Magali García Ramis (Puerto Rico) -- In foreign parts / Thea Doelwijt (Suriname) -- Little ants / J.M. Sanz Lajara (Dominican Republic) -- Sketches in transt...going home / Dionne Brand (Trinidad) -- The parade ends / Reinaldo Arenas (Cuba)
"A Plume book."--Title page.
Includes bibliographical references (pages 273-278)
Keywords: Short stories, Carribean; Carribean fiction -- 20th century